1995
DOI: 10.1080/00288330.1995.9516644
|View full text |Cite
|
Sign up to set email alerts
|

Induction of triploid embryos by heat shock in the Chilean northern scallopArgopecten purpuratusLamarck, 1819

Abstract: Triploidy in embryos of the Chilean northern scallop, Argopecten purpuratus Lamarck, 1819, was induced with heat shock. Ploidy levels were assessed by chromosome counting after 3 h from embryos at the 8-16 cell stage of development. The efficiency of induction varied with the time of treatment post-insemination and the temperature of the shock. The duration of the shock showed a positive correlation with the percentage of triploids, the highest of which was obtained using 31°C for 15 min applied 10 min after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…The percentage of triploid larvae obtained in this study (14% and 39%) are lower than those reported for other scallop species using the same inductors, but they are within the range previously obtained in preliminary studies (5%-58%; Beaumont, 1986;Canello et al, 1992;Ruiz-Verdugo et al, 2000;Winkler et al, 1993). This suggests that results can be improved by optimizing the induction protocols (Surier et al, 2007;Toro et al, 1995). (Desroisers et al, 1993;G erard, Naciri, Peignon, Ledu, & Phelipot, 1994).…”
Section: Post-larvae Survival and Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of triploid larvae obtained in this study (14% and 39%) are lower than those reported for other scallop species using the same inductors, but they are within the range previously obtained in preliminary studies (5%-58%; Beaumont, 1986;Canello et al, 1992;Ruiz-Verdugo et al, 2000;Winkler et al, 1993). This suggests that results can be improved by optimizing the induction protocols (Surier et al, 2007;Toro et al, 1995). (Desroisers et al, 1993;G erard, Naciri, Peignon, Ledu, & Phelipot, 1994).…”
Section: Post-larvae Survival and Growthmentioning
confidence: 99%
“…There are several examples of studies on triploidy induction on scallops, including species such as Argopecten irradians (Cogswell, Kenchington, Roach, & MacDonald, ; Tabarini, ; Zarnoch, Surier, Karney, Schreibman, & Gamss, ), A. purpuratus (Canello, Paredes, & Toro, ; Lohrmann & von Brand, ; Toro, Sanhueza, Paredes, & Canello, ; Winkler, Ladrón de Guevara, Estévez, & Jollán, ), A. ventricosus (Ruiz‐Verdugo, Allen, & Ibarra, ; Ruiz‐Verdugo, Ramírez, Allen, & Ibarra, ), Chlamys nobilis (Komaru, Uchimura, Ieyama, & Wada, ; Zeng et al., ), C. farreri (Yang, Zhang, & Guo, ), C. varia (Barón, Diter, & Bodoy, ), Nodipecten subnodosus (Maldonado‐Amparo, Ramírez, Ávila, & Ibarra, ), Patinopecten yessoensis (Meng et al., ; Yang, Li, & Guo, ), Pecten maximus (Beaumont, ), and Placopecten magellanicus (Desroisers et al., ). The efficiency of triploidy induction varies with different species and techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the post-nineties increase in scallop production, culture technologies have improved (Winkler et al, 1993;Toro et al, 1995a;Uriarte et al, 1996a;Ortiz et al, 2002). As a result of the post-nineties increase in scallop production, culture technologies have improved (Winkler et al, 1993;Toro et al, 1995a;Uriarte et al, 1996a;Ortiz et al, 2002).…”
Section: Evolution and Information Requiredmentioning
confidence: 99%
“…Triploid scallop induction has been performed in many species, such as C. farreri (Yang, Zhang, & Guo, ; C. C. Zhang et al, ), Chlamys varia (Barón, Diter, & Bodoy, ), C. nobilis (Komaru & Wada, ; Lin et al, ), A. ventricosus (Ruiz‐Verdugo, Allen, & Ibarra, ; Ruiz‐Verdugo et al, ), A. irradians (Tabarini, ; Yu et al, ), A. nucleus (Barreto‐Hernández, Velasco, & Winkler, ), A. purpuratus (Lohrmann & von Brand, ; Toro, Sanhueza, Paredes, & Canello, ), P. yessoensis (Chang et al, ; Meng et al, ; Z. C. Wang et al, ; Yang et al, ; Zhao, ), Pecten maximus (Beaumont, ), Placopecten magellanicus (Desroisers et al, ), and Nodipecten subnodosus (Maldonado‐Amparo, Ramírez, Ávila, & Ibarra, ). In addition, allotriploid hybrids like C. farreri ♀ × A. irradians ♂ (Meng et al, ) and C. farreri ♀ × P. yessoensis ♂ (Du, Yang, Liu, Zhou, & Wang, ) have also been developed.…”
Section: Introductionmentioning
confidence: 99%